Challenges for Science and Technology development from economic integration - Bao, Mai Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The world economic integration will open the chances of integration for Vietnam to get access to the world’s development achievements, promote its specific advantages in the context of globlization. This puts also, from another side, many challenges because the process opens the cooperation accompanied with the tough competition of intersets. One of the most hard problems we have to face in the process of international integration include the S&T related challenges. Code: 11041702